Diverse presentation of connective tissue disorders in pregnancy - Bedi, Mini; Kaur, Sandeep; Patil, Prashant; Kaur, Kamaljeet; Kaur, Harbhajan; Kaur, Harkiran (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Connective tissue disorders (CTD) include a variety of chronic multisystem disorders including autoimmune conditions. Many of these conditions affect women of childbearing age and therefore pregnancy poses an important challenge for the caregivers. The precise knowledge of therapeutic safety and the effect of disease on pregnancy and vice versa are important to achieve best outcome. Hence, it is imperative to have a vast knowledge of disease with proper preconception counselling. We report series of cases of connective tissue disorders in pregnancy: tuberous sclerosis (TS), systemic lupus erythmatosis (SLE) and neurofibromatosis (NF) type 1. The first case with tuberous sclerosis was associated with obstetric complications. In both cases of SLE, we observed preterm delivery and IUGR. However, the course of SLE remained the same in both the cases. The case with NF 1 taught us that a normal obstetric outcome could be expected in pregnant women.